Mirror Nuclei of 17O and 17F in Relativistic and Nonrelativistic Shell Model - M. Mousavi; M. R. Shojaei (Advances in High Energy Physics)
We have investigated energy levels mirror nuclei of the 17O and 17F in relativistic and nonrelativistic shell model. The nuclei 17O and 17F can be modeled as a doubly magic 17O = n + (N = Z = 8) and 17F = p + (N = Z = 8), with one additional nucleon (valence) in the ld5/2 level. Then we have selected the quadratic Hellmann potential for interaction between core and single nucleon. Using Parametric Nikiforov-Uvarov method, we have calculated the energy levels and wave function in Dirac and Schrodinger equations for relativistic and nonrelativistic, respectively. Finally, we have computed the binding and excited energy levels for mirror nuclei of 17O and 17F and compare with other works. Our results were in agreement with experimental values and hence this model could be applied for similar nuclei.